Deixis Analysis on Oxford University E-mail Messages - Desi Nur Azizah; Yuliyanto Sabat; Lailatul Musyarofah; Endah Alamsari A. (Universitas Muhammadiyah Barru, 2024)
Deixis is essential to creating effective communication. This research aimed (i) to determine the number of each type of deixis contained within E-mails from Oxford University Publications Office and (ii) the meanings contained there in. This research used qualitative descriptive method. The basic theory used by researchers is the theory of Yule. Yule described deixis as divided into 3, namely person, spatial, and temporal.The data used in this study came from one of the sources who received an E-mail from Oxford University and interview data. The result of the research was there are 2 types of deixis in E-mail, namely person deixis and spatial deixis. In person deixis was found 29 data with 3 forms of pronouns, namely You, Your, We, Our, Us, Their, and It. In spatial deixis was found 3 data with 2 forms, namely below and this. From the interview data, the researchers found that the language used in international campuses generally easy to comprehend, particularly noting the helpfulness of deixis in grasping message meanings, albeit sometimes requiring repeated reading for full understanding, with messages from Oxford University being notably straightforward.